Method of Calculating Secondary Porosity of Reef Limestone Reservoir by Casting Thin Section Calibrating Nuclear Magnetic T2 Spectrum. (14th April 2021) - Zhao, Bin; Li, Zhaoping; Gao, Chuqiao; Zhang, Guoyi; Wu, Jinbo; Gao, Gang; Tang, Yang
Abstract : Secondary pores are the main reservoir space and transportation channel of oil and gas in reef limestone reservoir. At present, the main method of calculating secondary porosity is restricted by the morphological characteristics of porosity spectrum, regional artificial influence, and accuracy of calculation. We present a new method for calculating secondary porosity of reef limestone reservoir by the nuclear magnetic resonance T 2 spectrum which is calibrated by casting thin section. We begin with analyzing and determining the high correlation between the surface porosity of casting thin section and the total porosity. The objective is confirming the feasibility of the method of calculating secondary porosity by using thin-section information calibrate. Then, we use the surface porosity of thin section as the calibrating data and find the T 2 relaxation time corresponding to the best correlation between the secondary porosity and the secondary surface porosity of casting thin section, that is, the T 2 cutoff value of secondary porosity, through the Monte Carlo method. Finally, we calculate the secondary porosity by using the functional relationship between the secondary surface porosity and the surface porosity. The statistical analysis shows that the method of calculating secondary porosity effectively improves the calculation accuracy of secondary porosity. The secondary porosity calculation results have a high correlation with the reservoir productivity.